Comparison of wild almond plantation on north and south aspects of degraded forest in Zagros region of Iran - Y'ghoob Iranmanesh; Hasan Jahanbazi Gojani (تحقیقات جنگل و صنوبر ایران, 2007)
This research was conducted on north and south aspects in plantation site of Wild Almond  (Amygdalus scoparia Spach) in Mishan region at Chaharmahal and Bakhtiari province. At the first step, 50 shrubs of A. scoparia were selected randomly in each aspect. After that, quantitative charactereistics such as height, collar diameter, crown diameter and number of coppice sprouts were measured. The results indicated that the mean height, collar diameter, crown diameter and number of coppice sprouts in north aspect was significantly more than those in south aspect. The results of this research might help the foresters to establish a more desirable plantation with wild almond on the degraded forests.